2020
DOI: 10.4047/jap.2020.12.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different surface treatments on the shear bond strength of luting cements used with implant-supported prosthesis: Anin vitrostudy

Abstract: The aim of this study was to investigate the shear bond strength of luting cements used with implant retained restorations on to titanium specimens after different surface treatments. MATERIALS AND METHODS. One hundred twenty disc shaped specimens were used. They were divided into three groups considering the surface treatments (no treatment, sandblasting, and oxygen plasma treatment). Water contact angle of specimens were determined. The specimens were further divided into four subgroups (n=10) according to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…17 As Protemp is based on bis-acrylic composite, it has been advised not to use a cement that contains eugenol should not be used. 29 The findings of this study support this recommendation. It was also found in this study that the sandblasting surface treatment applied to the bisacryl composite-based temporary restorative material increased the bonding of the eugenol-containing cement.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…17 As Protemp is based on bis-acrylic composite, it has been advised not to use a cement that contains eugenol should not be used. 29 The findings of this study support this recommendation. It was also found in this study that the sandblasting surface treatment applied to the bisacryl composite-based temporary restorative material increased the bonding of the eugenol-containing cement.…”
Section: Discussionsupporting
confidence: 72%
“…This finding is consistent with studies that have indicated that sandblasted surfaces create micro-retention areas by enhancing the adhesion of cements through mechanical locking. [27][28][29] In a study assessing the retentive properties of various temporary cements on temporary crowns, it was found that calcium hydroxide cements exhibited greater retention on polymethylmethacrylate resins compared to Tempond (Ca(OH)2: 795 kPa; Temp-Bond: 714 kPa). 30 The study also revealed that the shear bond strengths of calcium hydroxide cements, with the exception of CAD/CAM Group 3Bc and Imicryl Group 3Bc, were higher than those of Tempbond.…”
Section: Discussionmentioning
confidence: 99%
“…Developing a surface morphology that accelerates bone healing is one of the top interests in materials sciences and biotechnology. The high predictability and good results obtained in daily clinical practice through SLA surface treatment on Ti and Ti alloy implants, highlight this texturing method as one of the main techniques used in the market [ 11 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The poor bonding strength of the Control group may be due to the lack of resin phase. However, the direct relationship between the bonding strength and contact angle cannot be determined because of the confounding of hydrophilicity, wettability, and surface energy ( Degirmenci and Saridag, 2020 ). Ozcan et al ( Özcan et al, 2008 ) pointed out that MDP monomer could be directly bonded with metal oxides.…”
Section: Discussionmentioning
confidence: 99%